Oral (−)-Epicatechin Inhibits Progressive Tau Pathology in rTg4510 Mice Independent of Direct Actions at GSK3β - Hole, Katriona L.; Staniaszek, Lydia E.; Menon Balan, Gayathri; Mason, Jody M.; Brown, Jon T.; Williams, Robert J. (Frontiers in Neuroscience, 2021)
Aggregation of the microtubule-associated protein tau into paired helical filaments (PHFs) and neurofibrillary tangles is a defining characteristic of Alzheimer’s Disease. Various plant polyphenols disrupt tau aggregation in vitro but display poor bioavailability and low potency, challenging their therapeutic translation. We previously reported that oral administration of the flavonoid (−)-epicatechin (EC) reduced Amyloid-β (Aβ) plaque pathology in APP/PS1 transgenic mice. Here, we investigated whether EC impacts on tau pathology, independent of actions on Aβ, using rTg4510 mice expressing P301L mutant tau. 4 and 6.5 months old rTg4510 mice received EC (∼18 mg/day) or vehicle (ethanol) via drinking water for 21 days and the levels of total and phosphorylated tau were assessed. At 4 months, tau appeared as two bands of ∼55 kDa, phosphorylated at Ser262 and Ser396 and was unaffected by exposure to EC. At 6.5 months an additional higher molecular weight form of tau was detected at ∼64 kDa which was phosphorylated at Ser262, Ser396 and additionally at the AT8 sites, indicative of the presence of PHFs. EC consumption reduced the levels of the ∼64 kDa tau species and inhibited phosphorylation at Ser262 and AT8 phosphoepitopes. Regulation of the key tau kinase glycogen synthase kinase 3β (GSK3β) by phosphorylation at Ser9 was not altered by exposure to EC in mice or primary neurons. Furthermore, EC did not significantly inhibit GSK3β activity at physiologically-relevant concentrations in a cell free assay. Therefore, a 21-day intervention with EC inhibits or reverses the development of tau pathology in rTg4510 mice independently of direct inhibition of GSK3β.